Respiratory Muscle Strength Training. - Sapienza, Christine M. (Plural Publishing, Incorporated, 2020)
Respiratory Muscle Strength Training is a clinical guide, intended to provide clinicians with the background information they need to understand respiratory muscle strength training (RMST). With a variety of case studies provided by well-known authors and clinicians, this text acts as a guidebook to the RMST protocol and provides practical information for use in the field of healthcare. In addition to real-world case studies, Respiratory Muscle Strength Training includes a chapter devoted to Frequently Asked Questions, a representative sample of the devices commonly used for respiratory traini.